High-Performance Terahertz Coherent Perfect Absorption with Asymmetric Graphene Metasurface - Jintao Chen; Lujun Hong; Jiangtao Lei; Yun Shen; Xiaohua Deng; Jing Chen; Tianjing Guo (Photonics, 2024)
In this work, we introduce a novel coherent perfect absorber, accentuating its novelty by emphasizing the broad bandwidth, reduced thickness, tunable property, and straightforward design achieved through the use of an asymmetric graphene metasurface. This design incorporates both square and circular graphene patches arranged on either side of a silicon substrate. With an optimized structural design, this absorber consistently captures over 90% of incoming waves across the frequency range of 1.65 to 4.49 THz, with a graphene Fermi level of 0.8 eV, and the whole device measures just 1.5 um thick. This makes our absorber significantly more effective and compact than previous designs. The absorber’s effectiveness can be significantly enhanced by combining the metasurface’s geometric design with the graphene Fermi level. It is anticipated that this ultrathin, wideband coherent perfect absorption device will play a crucial role in emerging on-chip THz communication technologies, including light modulators, photodetectors, and so on.